Effects of Parental Work Conditions on Children’ School Achievement A Study of Dual- Earner Families in Malaysia - Talib, Johari (ACTIVIDAD FÍSICA Y CIENCIAS / PHYSICAL ACTIVITY AND SCIENCE, 2009)
The purpose of this study is to analyze relationships between parental (dual-earner families) work conditions (work conditions, work hours, work tempo), parenting styles (parenting styles and parental involvement), children’s task engagement behaviour and school achievement. This study takes account the demographic changes in Malaysian families as result of urbanization and industrial-economic based. The study was conducted using survey method approach based on human ecology theory employed 200 dual earner families as sample. Using path model analysis, the study indicates number of consistent relationships between demographic variables, parenting styles, children’s task engagement behaviour and school achievement. Effects of mothers’ and fathers’ work conditions, parenting styles on children’s behaviour and school achievement were about similar. Overall, parental work conditions, parental authoritarianism, parental authoritativeness, parental involvement, socioeconomic status (parental job status, salary, parental education) had strong effects on children’s task engagement behaviour and school achievement. Children’s task engagement behaviour also found to have strong effect on children’s school achievement.